Periprocedural Results and Right Ventricular Outcomes of Computer Assisted Vacuum Thrombectomy Treatment of Acute Pulmonary Embolism: Interim Analysis of 300 Patients From the STRIKE‐PE Study - Moriarty, John M.; Schiro, Brian J.; Dohad, Suhail Y.; Tamaddon, Houman; Davis, Hugh C.; Shavelle, David M.; Chrysant, George S.; Iliadis, Elias A.; Dexter, David J.; Ciampi Dopazo, Juan J.; Holden, Andrew; West, Frances M.; et al. (Journal of the American Heart Association, 2025)
Pulmonary embolism (PE) can be a life-threatening condition. Endovascular treatment is emerging as a promising treatment to restore hemodynamic stability and reverse right ventricular (RV) dysfunction in PE; however, more studies are needed to elucidate the effects on the right ventricle after endovascular treatment. This analysis reports the effects of computer assisted vacuum thrombectomy on RV function. Eligible patients for the single-arm, prospective, international, multicenter STRIKE-PE (A Prospective, Multicenter Study of the Indigo Aspiration System Seeking to Evaluate the Long-Term Safety and Outcomes of Treating Pulmonary Embolism) cohort study are adults with acute PE with symptoms for ≤14 days and an RV/left ventricular ratio of ≥0.9 who are treated with computer assisted vacuum thrombectomy. Reported here are periprocedural and RV outcomes of the initial 300 patients of STRIKE-PE, to provide insights into effects on RV function after computer assisted vacuum thrombectomy. Patients were classified with high-risk (5.7%), intermediate-high-risk (84.7%), or intermediate-low-risk (9.7%) PE. Median thrombectomy time was 30 minutes. Mean on-table systolic pulmonary artery pressure decreased from 51.7 mm Hg to 41.3 mm Hg, a 19.1% reduction ( <0.001). The change in mean RV/left ventricular ratio from baseline to 48 hours postprocedure (primary effectiveness end point) was a decrease from 1.40 to 0.99, a 26.8% reduction ( <0.001). Clinical parameters and echocardiographic measures of right heart strain improved from baseline to 48 hours postprocedure ( <0.001). The rate of composite major adverse events within 48 hours postprocedure (primary safety end point) was 2.0%. Median Borg dyspnea scale at rest decreased from 4.0 at baseline to 0.5 at discharge ( <0.001). This interim analysis demonstrates that computer assisted vacuum thrombectomy safely and expeditiously improves hemodynamic status, RV function, and perceived dyspnea. https://clinicaltrials.gov; Unique Identifier: NCT04798261.